Effective School Principal Leadership and Teacher Performance (Current Research in Education: Conference Series Journal, 2024)
The principal as a leader has an important role in managing the school. In carrying out his role, the school principal is responsible for the success of the implementation of education both administratively and in developing human resources. Implementation is not an easy thing, it requires effort so that the implementation of leadership can run as expected. The literature review is the author's attempt to analyze various research results on good school principal leadership. Effective leadership can work with the principal's role in creating a positive climate, always directing and developing professional teachers and good communication with personnel in the school. Good control from the school principal over teacher performance is one of the efforts to achieve school success in creating quality learning according to school goals.